Mechanical drawing - French, Thomas Ewing 1871-1944. (New York McGraw-Hill, 1985)
A textbook introducing the basic theory, techniques, and uses of drafting for industrial arts and vocational high school students.
Includes index.
Keywords: Mechanical drawing; Mechanical drawing